The perturbation of PAHs on mosses in Aberdeen, Scotland, as a consequence of social restrictions imposed during the COVID-19 pandemic - Daniya, Thomas S.; Bowden, Stephen A. (Frontiers in Geochemistry, 2024)
Air quality and the concentration of polycyclic aromatic hydrocarbons (PAHs) in urban environments are increasingly becoming a concern. Measuring air quality and PAHs, and linking these to specific activities, requires deploying and recovering sampling devices to capture and measure any changes. From May 2020 to June 2021, during the “lockdown” period of the COVID-19 pandemic, acrocarpous and pleurocarpous mosses were collected from five types of site in Aberdeen, United Kingdom, and the concentration of PAHs measured to track changes in PAHs as travel-related activities changed. The predominant types of PAHs found on mosses were of the four- and five-ring varieties, with the four-ring variety of PAH (medium molecular weight) becoming more dominant as the lockdown was lifted. However, for most sites, the concentration of PAHs was evidently perturbed by the transient lifting, reimposing, and then lifting of lockdown conditions, which either directly limited travel or changed people’s motivations to travel by car. Molecular diagnostic ratios or molecular marker parameters used to infer the source of PAHs varied little and were nearly always consistent with PAHs deriving from combustion in vehicle engines. Thus, even when travel was limited, PAHs were still derived from vehicle usage, although the overall concentrations on mosses were much lower. On average, the lowest PAH concentrations were found on mosses collected from a recreational park located the furthest from traffic. The highest PAH concentrations were observed on mosses collected from residential car parks during periods when the lockdown had been lifted. However, mosses from the same residential car parks had very low PAH concentrations during periods of travel restrictions, strongly suggesting that, for mosses, local factors and patterns of vehicle usage strongly determine their exposure to PAHs. Therefore, mosses within urban environments can be used for monthly monitoring of PAHs as they are able to detect changes induced by human behaviour.